2014
DOI: 10.1111/jch.12328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moderate Aerobic Exercise Training on Vascular Health and Blood Pressure in African Americans

Abstract: As healthcare progresses toward individualized medicine, understanding how different racial groups respond to lifestyle interventions is valuable. It is established that African Americans have disproportionate levels of cardiovascular disease and impaired vascular health, and clinical practice guidelines suggest lifestyle interventions as the first line of treatment. Recently, we reported six months of aerobic exercise improved inflammatory markers, flow-mediated dilation (FMD), and levels of circulating endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 41 publications
2
33
1
4
Order By: Relevance
“…Previous studies in HIV-uninfected adults suggested that short term exercise training can improve endothelial function and vascular remodeling 41 . Additionally, enrollment in an exercise program improved FMD in young patients who were prehypertensive (aged 18–35) and overweight patients with coronary heart disease 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in HIV-uninfected adults suggested that short term exercise training can improve endothelial function and vascular remodeling 41 . Additionally, enrollment in an exercise program improved FMD in young patients who were prehypertensive (aged 18–35) and overweight patients with coronary heart disease 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Kebiasaan olahraga, terutama aerobik, penting pada prevensi aterosklerosis. Hasil penelitian pada orang Afrika Amerika, menunjukkan bahwa melakukan aerobik selama 8 minggu atau 6 minggu dapat memperbaiki struktur dan fungsi vaskuler (6). Kapasitas pengambilan oksigen maksimal disesuaikan dengan berat yang berbanding terbalik dengan CIMT.…”
Section: Hubungan Antara Cimt Dengan Faktor Risiko Kardiovaskuler unclassified
“…On the prevalence of different types of breed, Feairheller et al (28) point out that according to the American Heart Association (AHA), African-Americans have a higher prevalence in cardiovascular diseases and greater oxidative stress and inflammation levels in endothelial cells compared to Caucasian individuals.…”
mentioning
confidence: 99%